PENGARUH MODEL PEMBELAJARAN DARING (DENGAN PEMUTARAN VIDEO) TERHADAP PEMAHAMAN KONSEP TERJADINYA BENCANA ALAM (KEBAKARAN DAN GEMPA BUMI) PADA INSTITUSI PENDIDIKAN KESEHATAN “X” DI KOTA SURABAYA - M. Usa, WD. Yuni; Andreas Pradhana; Juni Dwi Kurnia Santi; Enny Mar’atus Sholihah; Vebiola Dammu Djari; Anisa Nomeni; Kifri Aquinas (Rena Cipta Mandiri, 2025)
Online learning is an alternative way to improve the effectiveness of understanding a concept. The purpose of this study was to determine the effect of the online learning model using video playback on the understanding of the concept of natural disasters (fires and earthquakes) in students of the health education institution